YOGA- A Holistic Approach For Stress Management In Dentistry - “Part And Parcel Of Life” - Gupta, Neetika; Verma, Sherry; Khurana, Aman; Sharma, Siddharth; Gill, Jaipreet Singh (International Research Journal of Ayurveda & Yoga, 2021)
Dentistry is a very challenging and demanding profession. It is always related with some occupational menaces like physical stress i.e. musculoskeletal problems and stress‑related problems. The numerous occupation hazards, the dentist encounters are the spinal complications like cervical spondylosis, tendonitis, thoracic kyphosis, arthritis, etc. Also chances of stress related issues are more as they deal with long list of patients, and complicated treatment of procedures leads to different posture problems and leads to continuous strain on the body Hence, there is a dire need for implementation of yogic practices as an anxiolytic agent to lead a healthy and pain free lifestyle. The practice of yoga has been proven to be efficacious in management of quite a lot of stress and lifestyle disorders. It strengthens one physically, mentally, and emotionally. Yoga emphases on physical body, mind and breathing. Asanas (physical postures), Pranayama (breathing techniques) and meditation accomplish the motive behind the need of yoga in dentist’s lifestyle. Yoga averts the diminishing of cellular immunity that is evident in mental and physical stress. Yoga is mandatory, enjoyable, convenient, versatile, and highly beneficial and a great way for dentists and their patients to fight off stress and anxiety and to lessen the occupation related musculoskeletal problems. The aim and objective of this review is to bring in to light, the anxiolytic effect of yoga and its efficiency in decreasing the stress levels in dentist’s life.